Flavin Conjugated Polydopamine Nanoparticles Displaying Light-Driven Monooxygenase Activity - Crocker, Leander; Fruk, Ljiljana (Frontiers in Chemistry, 2019)
A hybrid of flavin and polydopamine (PDA) has been explored as a photocatalyst, drawing inspiration from natural flavoenzymes. Light-driven monoxygenase activity has been demonstrated through the oxidation of indole under blue light irradiation in ambient conditions, to afford indigo and indirubin dyes. Compared to riboflavin, a flavin-polydopamine hybrid is shown to be more resistant to photobleaching and more selective toward dye production. In addition, it has been demonstrated that it can be recycled from the solution and used for up to four cycles without a marked loss of activity, which is a significant improvement compared to other heterogenous flavin catalysts. The mechanism of action has been explored, indicating that the PDA shell plays an important role in the stabilization of the intermediate flavin-peroxy species, an active component of the catalytic system rather than acting only as a passive nanocarrier of active centers.